CRE firms' refinancing and cash flows at a time of high inflation - Christian Bjørland (Norges Bank, 2023)
Norwegian banks have substantial exposures to commercial real estate (CRE), and developments in the industry are important for financial stability. Higher financing costs, falling CRE prices and a large amount of bond debt maturing in the coming years have increased the refinancing risk associated with CRE over the past year. We use a broad set of data sources to assess CRE firms' refinancing risk and their capacity to absorb higher financing costs. The strong growth in CRE firms' bond debt over the past decade has contributed to spreading risk from banks to other financial operators. At the same time, bond debt can be a less stable funding source than bank debt in turbulent times. We find that banks have modest exposures to CRE groups with elevated refinancing risk in the bond market and those with the weakest financial strength. The rapid rise in rents over the past few years and CPI-indexing of office leases make many CRE firms robust against higher interest rates and credit premiums. In the event of an economic downturn, however, developments in renteal income may fall.
hdl:11250/3166345
Keywords: 330; Financial stability; commercial real estate (CRE); banks' credit risk; Gewerbeimmobilien; Refinanzierung; Immobilienwirtschaft; Norwegen